PENDIDIKAN MODERASI BERAGAMA SEBAGAI INSTRUMEN MITIGASI PERUNDUNGAN MELALUI GERAKAN GANTRUNG SABUMI - Adelia Nanda Putri Astiyan; Nirma Romadlon; Faiqotus Silvi Azka Mu’tiya; Ika Maulidatusy Syarifah; Mohammad Makinuddin (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2024)
This study aims to analyze the implementation, supporting and inhibiting factors, and the impact of religious moderation education within the Aksi Gantrung Sabumi Anti-Bullying Movement at State Junior High School 1 Mejayan. This study employs a qualitative approach using a case study design. Data collection techniques included observation, interviews, and documentation. Data were analyzed using the Miles and Huberman model through data reduction, data presentation, and drawing conclusions. The results indicate that religious moderation education is implemented through educational, participatory, and structural approaches, such as anti-bullying declarations, anti-bullying campaigns, the formation of change agents, character development, and the ASAKU reporting system. Supporting factors for the program include a conducive school culture, teacher involvement, parental support, and the cultivation of religious and social character. Meanwhile, inhibiting factors stem from the influence of social media, the environment outside of school, and the unstable emotional state of students. Program implementation yields positive impacts, including increased tolerance, the courage to report bullying incidents, improved collaboration skills, and a decrease in bullying behavior within the school environment. This study demonstrates that religious moderation education holds strong relevance in fostering a safe, inclusive, and bullying-free school culture.